DUALISME DI LINGKUNGAN PERUSAHAAN INTI RAKYAT(PIR) LOKAL TEH DI JAWA - Siti Hamidah; Sri Widodo (Agro Ekonomi, 1978)
This research aimed to analyse dualism between plasm farmers and nucleus estate in the Tea Local Nucleus Estate Smallholder Scheme at Java. The study is conducted in West and Center of Java Provinces. Data of 330 household samples are analyzed by Proportion Test.Although most of plasm fanners have the technical cropping and the use of input and labour are lower than nucleus estate, but the gapa on productivity, product quality, income of tea farming, and fanning efficiency are small.There is still dualism in the Tea Local Nucleus Estate Smallholder Scheme at Java, but it tends to decline. This gap become smaller between Smallholder Scheme could make smaller distance between smallholder plantation and estate.